THE SEASONAL EFFECTS OF DECIDUOUS TREE FOLIAGE IN CORS-GNSS MEASUREMENTS (VRS/FKP) - Pirti, Atinc (UNIV OSIJEK, TECH FAC, 2016)
This article examines the performance and use of GNSS based data acquisition systems in the seasonal effects of deciduous tree foliage. As a general rule, a clear view of the sky is preferred when using GNSS for determining location. Season in the case of deciduous trees is the parameter affecting GNSS signal attenuation. As a result of this attenuation, positions computing weak signals tend to be less accurate. This means that using GNSS in forest is one of the most demanding uses of technology and one that requires particular attention when evaluating GNSS receivers that will be used in such an environment. This paper evaluates GNSS positional accuracy, precision and performance in the forest area. The obtained horizontal differences for three baselines in April between CORS-VRS/FKP and Total station survey results are +/-(1 divided by 3) cm. The height differences obtained for three baselines in April between CORS-FKP and Total station survey results are +/-(2 divided by 4) cm.
Keywords: accuracy; CORS; FKP; GNSS; RTN; season; VRS; FOREST; GPS; Engineering